2017
DOI: 10.1515/nor-2016-0391
|View full text |Cite
|
Sign up to set email alerts
|

Performing the Self in the Mainstream

Abstract: Blogging has become an integral part of girls' media culture in Norway. This article investigates how teenage girls in the mainstream blogging community perform selves in their blogs over time. While studies of girls' self-presentations online abound, most draw solely on analyses of online artefacts and lack a temporal perspective. To address these gaps, this investigation has employed a longitudinal design combining in-depth interviews with ethnographic content analyses of blogs, and has analysed girls' onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…Flera forskare har menat att den kritik bloggerskorna bemöttes av kan ses som en upprepning av en bekönad diskurs där kvinnors och unga tjejers aktiviteter trivialiseras genom att beskrivas som negativa och ytliga. Tvärtom kan bloggande förstås som ett sätt att ta makten över de förväntningar på femininitet som finns i omlopp (Dmitrow-Devold 2017, Hänninen 2015, Lövheim 2011a). Modebloggande uttrycker den ambivalens som nutida föreställningar om såväl femininitet som feminism gestaltas med.…”
Section: Femininitet Och Intimitet Som Företagandeunclassified
“…Flera forskare har menat att den kritik bloggerskorna bemöttes av kan ses som en upprepning av en bekönad diskurs där kvinnors och unga tjejers aktiviteter trivialiseras genom att beskrivas som negativa och ytliga. Tvärtom kan bloggande förstås som ett sätt att ta makten över de förväntningar på femininitet som finns i omlopp (Dmitrow-Devold 2017, Hänninen 2015, Lövheim 2011a). Modebloggande uttrycker den ambivalens som nutida föreställningar om såväl femininitet som feminism gestaltas med.…”
Section: Femininitet Och Intimitet Som Företagandeunclassified
“…The influencers who were interviewed had starting blogging so as to create “a room‐of‐their own,” and to share their personal thoughts and passions with others (see also Dmitrow‐Devold, 2017; Lövheim, 2011; Palmgren, 2015). The connections that they developed through their online activities quickly allowed them to use their private homes and families as a backdrop for product placement.…”
Section: Lifestyle Influencersmentioning
confidence: 99%
“…Goffman's (1959) dramaturgical approach is a fruitful framework through which to examine the dynamics of self-presentation on social media as performance (e.g. Azariah 2016;Dmitrow-Devold 2017). By understanding this in terms of a front stage and back stage, where the latter is the place where individuals retreat and step out of their role and thus where a more authentic self resides, Goffman emphasizes the rather porous dichotomy between the public and the private.…”
Section: Please Consult the Published Version To Ensure Correct Citationmentioning
confidence: 99%
“…It has also been suggested that the essence of blogging is a form of vanity culture enacting social ranking, in a rat race for maximum attention and slick self-promotion (Lovink 2008). In a study looking at how Norwegian teenage female bloggers perform selves in their blogs over time, Dmitrow-Devold (2017) finds that the girls To appear in: Tovares and Gordon (eds) 2020: "Identity and ideology in digital food discourse: Social media interactions across cultural contexts" Bloomsbury.…”
Section: Please Consult the Published Version To Ensure Correct Citationmentioning
confidence: 99%